Strategi Peningkatan Keterampilan Pertukangan Kayu Sebagai Upaya Pemberdayaan Ekonomi Masyarakat Desa Mudik - Dermawan Zebua; Hamedoni Harita; Bimawijaya Laia; Muhammad Haris Zalukhu; Serta Denius Daeli; Ikhtiar Aronifati Daeli; Jun Fajar Krisman Giawa; Kevin Berkat Mendrofa; Friski Dermawan Zebua; Rifki Wahyudi Mendrofa; Jefri Rahmat Daeli (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
The carpentry training program in Mudik Village aims to improve the technical and entrepreneurial skills of the community as part of local economic empowerment efforts. The three-day training program utilizes a combination of theory and practice. The first day focused on theoretical material, including an introduction to wood types, equipment usage, measurement techniques, occupational safety principles, and entrepreneurial fundamentals. The second and third days focused on hands-on practice in making simple products, such as bookshelves, covering the measuring, cutting, assembly, and finishing processes. Evaluation results showed significant skill improvements across all aspects, with the greatest improvement in the ability to use modern tools (+64%). Furthermore, participants demonstrated increased awareness of occupational safety and understanding of product marketing strategies. This training demonstrated that the three-day, integrative approach can improve skills while motivating the community to develop carpentry businesses. Future recommendations include further training, business mentoring, and the formation of village business groups to support the program's sustainability.